CONTRIBUTIONS OF CHILDREN'S LITERATURE IN THE LITERACY PROCESS - dos Santos, Janaína Camargo; Galhart, Anna Carolina (Seven Editora, 2025)
This article aims to analyze the contributions of Children's Literature to the literacy process, its benefits for the formation of readers and the development of a critical subject. This is a qualitative research, with the foundation of the literature review, bringing references in the areas of literacy and Children's Literature: COELHO, FARIA, FERNANDES, LAJOLO, SILVA, SOARES and ZILBERMAN. The importance of the teacher to stimulate the desire for reading is emphasized, seeking a methodology that favors the process of literacy and literacy, in a precise way, and that triggers the formation of the child's identity. The study about the literacy process and its social aspects, points out as relevant the formation of the teacher as a reading subject and trainer of new readers and the Children's Literature book as a pedagogical resource of this new process that stimulates the contextualization, imagination and creativity of students at the beginning of schooling.DOI: https://doi.org/10.56238/sevened2024.037-121